The sylvatic transmission cycle of Trypanosoma cruzi in a rural area in the humid Chaco of Argentina - Alvarado Otegui, Julián Antonio (2012)
Little is known about the sylvatic transmission cycle of Trypanosoma cruzi in the Gran Chaco ecoregion. We conducted surveys to identify the main sylvatic hosts of T. cruzi, parasite discrete typing units and vector species involved in Pampa del Indio, a rural area in the humid Argentinean Chaco. A total of 44 mammals from 14 species were captured and examined for infection by xenodiagnosis and polymerase chain reaction amplification of the hyper-variable region of kinetoplast DNA minicircles of T. cruzi (kDNA-PCR). Ten (22.7%) mammals were positive by xenodiagnosis or kDNA-PCR. Four of 11 (36%) Didelphis albiventris (white-eared opossums) and six of nine (67%) Dasypus novemcinctus (nine-banded armadillos) were positive by xenodiagnosis and or kDNA-PCR. Rodents, other armadillo species, felids, crab-eating raccoons, hares and rabbits were not infected. Positive animals were highly infectious to the bugs that fed upon them as determined by xenodiagnosis. All positive opossums were infected with T. cruzi I and all positive nine-banded armadillos with T. cruzi III. Extensive searches in sylvatic habitats using 718 Noireau trap-nights only yielded Triatoma sordida whereas no bug was collected in 26 light-trap nights. Four armadillos or opossums fitted with a spool-and-line device were successfully tracked to their refuges; only one Panstrongylus geniculatus was found in an armadillo burrow. No sylvatic triatomine was infected with T. cruzi by microscopical examination or kDNA-PCR. Our results indicate that two independent sylvatic transmission cycles of T. cruzi occur in the humid Chaco. The putative vectors of both cycles need to be identified conclusively.